Interfacial and confined molecular-assembly of poly(3-hexylthiophene) and its application in organic electronic devices - Junhao Liang; Xing Ouyang; Yan Cao (Science and Technology of Advanced Materials)
Poly(3-hexylthiophene) (P3HT) is a typical conducting polymer widely used in organic thin-film transistors, polymer solar cells, etc., due to good processability and remarkable charging carrier and hole mobility. It is known that the ordered structure assembled by π-conjugated P3HT chains could promote the performance of electronic devices. Interfacial and confined molecular-assembly is one effective way to generate an ordered structure by tuning surface geometry and substrate interaction. Great efforts have been made to investigate the molecular chain assembly of P3HT on a curved surface that is confined to different geometry. In this report, we review the recent advances of the interfacial chain assembly of P3HT in a flat or curved confined space and its application to organic electronic devices. In principle, this interfacial assembly of P3HT at a nanoscale could improve the electronic properties, such as the current transport, power conversion efficiency, etc. Therefore, this review on interfacial and confined assembly of P3HT could give general implications for designing high-performance organic electronic devices.